FAKTOR-FAKTOR YANG MEMPENGARUHI KESELAMATAN LATIHAN TERBANG: KELELAHAN FISIK, CUACA, KELAYAKAN PESAWAT LATIH - Nurhadi, Kausal Wisa; Bagastya, Made; Noorwahyu, Arsanto (Kohesi: Jurnal Sains dan Teknologi, 2025)
Safety during flight training is a fundamental aspect of aviation. Various factors can affect the level of safety, including the pilot's physical condition, weather factors and the fitness of the training aircraft. This article aims to evaluate the impact of these three factors on safety during flight training. The method used in this article is qualitative and library research. The results show that physical fatigue has a significant influence on the pilot's level of alertness and response when flying the aircraft. In addition, weather factors such as low visibility and turbulence also increase the risk of accidents and errors in maneuvers. The technical feasibility of the training aircraft, including regular maintenance and engine condition, also plays an important role in preventing potentially hazardous system failures. Overall, safety in flight training is greatly influenced by the physical readiness of the pilot, the conditions of the flight environment, and the technical aspects of the training aircraft. Therefore, physical fatigue management, weather monitoring and optimal aircraft maintenance should be prioritized in aviation.